La ecoética frente al mal del ecocidio - Nieto, Jaime Tatay (Cauriensia, 2023)
This article analyzes the way in which the various currents of ecological ethics, or ecoethics, have conceptualized environmental degradation and biodiversity loss and affirms that their most dramatic expression —ecocide— is an evil. In dialogue with theological ecoethics, I argue —in the face of the danger of moral monism that often permeates the ethical debate on sustainability— the desirability of adopting a pluralistic vision in which the various modes of ethical reasoning converge to denounce the evil of ecocide.